Group psychotherapy for breast cancer patients: a clinica approach - Die-trill, María (Psicooncología, 2007)
This article describes the different modalities of group psychotherapies that are most frequently used with breast cancer patients. In addition to documenting the efficacy of group psychotherapy in improving patients´ quality of life, physical symptoms and global psychological adaptation, emphasis is placed on clinical aspects of this treatment modality. Guidelines to develop effective groups are described. Only-session groups are described in detail in order to provide the health professionals with instruments that are clinically useful. Long duration and time-limited groups are equally described. Guidelines are offered to facilitate group development and help overcome the barriers that arise during this process. Finally, studies evaluating the effects of group participation on survival of breast cancer patients are included.